HAKIKAT PESERTA DIDIK - Kamaliah Kamaliah (CV. ADIBA AISHA AMIRA, 2025)
The term students are interpreted as people (children) who are following the process of educational activities or teaching and learning processes to grow and develop their potential, so in Arabic literature that is often used by Islamic education leaders, among others, they are found with the names: mutarabby, muta'allim, muta'addib, daaris, student. First, the word mutarabby implies as a person who is being targeted as a target to be educated in the sense of being created, maintained, regulated, managed, repaired through educational activities carried out together with murabby educators.